2018
DOI: 10.1136/jech-2017-209923
|View full text |Cite
|
Sign up to set email alerts
|

Teenage pregnancy and mental health beyond the postpartum period: a systematic review

Abstract: The association between teenage pregnancy and mental health beyond the postpartum period remains unclear. Future studies should employ age-period-cohort frameworks to disentangle effects of normative patterns and stress accumulation. Social factors are important in determining long-term mental health of teenage mothers and should be prioritised in prevention and intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 32 publications
(35 reference statements)
0
15
0
4
Order By: Relevance
“…Our review did not identify any primary studies in sub-Saharan Africa related to mental health, cognitive health, or educational outcomes of adolescent mothers affected by HIV. Globally, poor mental health has been found to be associated with adolescent pregnancy (Hodgkinson et al, 2014;LePlatte et al, 2012;McCracken & Loveless, 2014;Mitsuhiro et al, 2009), although a systematic review showed mixed results of the impact of adolescent pregnancy on long-term mental health (Xavier et al, 2018). Many adolescents affected by HIV face mental health challenges related to family grief and HIV stigma-by-association, which are also key issues for parenting adolescents (Amzel et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our review did not identify any primary studies in sub-Saharan Africa related to mental health, cognitive health, or educational outcomes of adolescent mothers affected by HIV. Globally, poor mental health has been found to be associated with adolescent pregnancy (Hodgkinson et al, 2014;LePlatte et al, 2012;McCracken & Loveless, 2014;Mitsuhiro et al, 2009), although a systematic review showed mixed results of the impact of adolescent pregnancy on long-term mental health (Xavier et al, 2018). Many adolescents affected by HIV face mental health challenges related to family grief and HIV stigma-by-association, which are also key issues for parenting adolescents (Amzel et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This synthesis suggests that young women recognise stress as profoundly impactful, and want to avoid it, but find that it is exacerbated by their socioeconomic situation. This emphasises the need for interventions that target social factors to impact long term mental health outcomes [69].…”
Section: Discussionmentioning
confidence: 99%
“…A local study revealed that this might be related to poor contraceptive knowledge and low socioeconomic status [ 38 ]. Moreover, teen child-bearing women are more likely to have lower educational growth, more adverse pregnancy complications, and even more postpartum depression [ 39 , 40 ]. In our study, infants of mothers aged <20 years had 2.81 times higher SIDS risk than those of mothers aged ≥20 years.…”
Section: Discussionmentioning
confidence: 99%